Pengaruh Integritas, Profesionalisme dan Kompetensi Auditor terhadap Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik (KAP) di Bandung - Turini Turini (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2021)
This study aims to examine the effect of integrity, professionalism and competence of auditors on audit quality at the public accounting firm in Bandung. Data were collected by distributing questionnaires with the convenience sampling technique to the respondents. While the sample used is the auditors who work at the Public Accounting Firm, Risman and Arifin, Dr. H.E. Suhardjadinata and Partners and Prof. Dr.H.tb Hasanudin, M.SC, and Partners who are domiciled in Bandung, totaling 35 samples. The analysis method used in this study is regression analysis with SPSS version 21 for Windows software. From multiple regressions, it produces three hypotheses that show its effect on audit quality, namely: integrity has a significant effect on audit quality. Professionalism has a significant effect on audit quality. Auditor competence has a positive significant effect on audit quality.